Signaling Function of Heme Oxygenase Proteins - Dennery, Phyllis A. (Mary Ann Liebert, Inc., 2014)
Significance: Many reports have underscored the importance of the heme degradation pathway that is regulated by heme oxygenase (HO). This reaction releases bile pigments and carbon monoxide (CO), which are important antioxidant and signaling molecules. Thus, the reaction of HO-1 would have significant cytoprotective effects. Nevertheless, the importance of this protein goes beyond its enzymatic action. New evidence outlines significant effects of inactive forms of the HO-1 protein. Recent Advances: In fact, the role of the HO protein in cellular signaling, including transcription factor activation, binding to proteins, phosphorylation, and modulation of protein function, among others, has started being elucidated. The mechanism by which the inducible form of HO-1, in particular, can migrate to various cellular compartments to mediate important signaling or how and why it binds to key transcription factors and other proteins that are important in DNA repair is also described in several physiologic systems. Critical Issues: The signaling functions of HO-1 may have particular relevance in clinical circumstances, including cancer, as redistribution of HO-1 into the nuclear compartment is observed with cancer progression and metastasis. In addition, along with oxidative stress, the pleiotropic functions of HO-1 modulate antioxidant defense. In organ transplantation, HO and its byproducts suppress rejection at multiple levels and in sepsis-induced pulmonary dysfunction, inhaled CO or modulation of HO activity can change the course of the disease in animals. Future Directions: It is hoped that a more detailed understanding of the various signaling functions of HO will guide therapeutic approaches for complex diseases. Antioxid. Redox Signal. 20, 1743–1753.